The relationship between modifiable health risk factors and health care costs for individuals who have completed a health risk assessment questionnaire for a South African health insurance scheme - Garbharran, Dinesh Hari Lall (My University, 2012)
Health care funders are seeking managed health care interventions to contain medical inflation. The purpose of this study is to assess the relationship between three health risk factors (smoking status, physical activity and body mass index (BMI)) and inpatient costs among health risk assessment (HRA) respondents at a South African health insurer. The results could inform the design of wellness programmes by ensuring that appropriate health risk factors are being targeted to reduce inpatient costs. This study utilises a two-part regression model to explore the relationships between the health risk factors and inpatient costs. The combined results of the two-part regression model indicate that increasing levels of physical activity and decreasing levels of BMI are associated with lower likelihoods of hospitalisation and lower magnitudes of inpatient costs for those that had a non-zero claim. The results of this study indicate no association between smoking cessation and lower inpatient costs.
M.Sc., Faculty of Science, University of the Witwatersrand, 2011
Keywords: Health risk assessment; Health promotion; Medical care, cost of